2016
DOI: 10.1080/07357907.2016.1227442
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Activation in Hepatic Stellate Cells Promotes Angiogenesis and Vascular Mimicry in Hepatocellular Carcinoma

Abstract: Previous studies have established that hedgehog (Hh) signaling mediates tumor-stroma interaction and promotes hepatocellular carcinoma progression. Here, we demonstrated that activation of Hh signaling in hepatic stellate cell (HSC) line LX-2 by Huh-7-derived sonic Hh led to increased secretion of angiogenic factors and promoted angiogenesis in vitro. The activated LX-2 also enhanced vascular mimicry of hepatoma cells. Furthermore, co-injection of Huh-7 and LX-2 significantly accelerated tumor growth with enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Hh also induces an epithelial to mesenchymal transition in malignant cells, favoring migration and invasiveness (Chen et al, 2014; Byrne et al, 2015). Finally, cancer-associated stromal cells release Hh ligands that promote malignant cell proliferation, angiogenesis and metastasis (Chan et al, 2014; Liu et al, 2016; Li et al, 2016). In human hepatocellular carcinoma, excessive Hh signaling occurs relatively frequently (Sicklick et al, 2006; Cheng et al, 2009; Al-Bahrani et al, 2015; Dugum et al, 2016), and the level of Hh pathway activity positively correlates with tumor size, invasion, chemoresistance, metastasis and mortality (Sicklick et al, 2006; Cheng et al, 2009; Chen et al, 2011; Lu et al, 2012; Che et al, 2012).…”
Section: Hedgehog Pathway In Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Hh also induces an epithelial to mesenchymal transition in malignant cells, favoring migration and invasiveness (Chen et al, 2014; Byrne et al, 2015). Finally, cancer-associated stromal cells release Hh ligands that promote malignant cell proliferation, angiogenesis and metastasis (Chan et al, 2014; Liu et al, 2016; Li et al, 2016). In human hepatocellular carcinoma, excessive Hh signaling occurs relatively frequently (Sicklick et al, 2006; Cheng et al, 2009; Al-Bahrani et al, 2015; Dugum et al, 2016), and the level of Hh pathway activity positively correlates with tumor size, invasion, chemoresistance, metastasis and mortality (Sicklick et al, 2006; Cheng et al, 2009; Chen et al, 2011; Lu et al, 2012; Che et al, 2012).…”
Section: Hedgehog Pathway In Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Hedgehog signaling pathway activation can promote tumor cell growth, migration, metastasis and in vivo tumorigenesis . In hepatic stellate cells, the Hedgehog signaling pathway is activated, which promotes hepatoma cell angiogenesis and vasculogenic mimicry . Previous studies have indicated that activated Hedgehog signaling has important functions in HCC occurrence and development.…”
Section: Introductionmentioning
confidence: 99%
“…The Hh signaling pathway has been implicated in the regulation of angiogenesis in normal tissues (77, 78) and cancer (79, 80) through induction of angiogenic factors including VEGFs and ANG1, 2. Examination of CD31 expression, a marker of endothelial cells, showed decreased blood vessel density in LAD tumors treated with anti-SHH/IHH 5E1 antibody compared to IgG 1 treated tumors (Fig.…”
Section: Resultsmentioning
confidence: 99%